2006
DOI: 10.1359/jbmr.060802
|View full text |Cite
|
Sign up to set email alerts
|

Change in Lumbar Spine BMD and Vertebral Fracture Risk Reduction in Teriparatide-Treated Postmenopausal Women With Osteoporosis

Abstract: Increases in lumbar spine BMD account for 30-41% of the vertebral fracture risk reduction with teriparatide treatment. The remaining fracture risk reduction is caused by improvements in non-BMD determinants of bone strength.Introduction: Changes in BMD account for a small percentage of the fracture risk reduction seen in patients treated with antiresorptive drugs. The relationship between changes in lumbar spine BMD and vertebral fracture risk reduction with teriparatide treatment has not been assessed. Materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
82
1
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 144 publications
(89 citation statements)
references
References 30 publications
(43 reference statements)
2
82
1
4
Order By: Relevance
“…(32) Various subgroups from these pivotal trials have been studied, showing that these two PTH forms are effective in subjects who have or have not previously fractured or have experienced a single fracture or multiple fractures, and that complaints of back pain are reduced. (20,(31)(32)(33)(34)(35) …”
Section: Pth Efficacymentioning
confidence: 99%
“…(32) Various subgroups from these pivotal trials have been studied, showing that these two PTH forms are effective in subjects who have or have not previously fractured or have experienced a single fracture or multiple fractures, and that complaints of back pain are reduced. (20,(31)(32)(33)(34)(35) …”
Section: Pth Efficacymentioning
confidence: 99%
“…(28) Moreover, discrepancy exists between aBMD changes in patients treated with anti-osteoporotic pharmaceuticals and the observed reduction in fracture risk. (29)(30)(31) Thus, accurate in vivo measures of bone strength may improve diagnostics and treatment monitoring. In a study using intact cadaver forearms, the relation between observed (ie, biomechanically measured) bone strength and aBMD (correlation coefficient [R 2 ] ¼ 0.31) was inferior to that of observed bone strength and failure load predicted from FEA (R 2 ¼ 0.66), (32) demonstrating that FEA biomechanical parameters provide information on bone strength beyond aBMD.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, although areal BMD measurements remain an established diagnostic tool for osteoporosis, improvement of BMD is insufficient when it comes to explaining the efficacy of an agent to reduce fracture risk. (27,28) We studied the ability of three currently available treatments, two inhibitors of bone resorption and one anabolic agent, to alter several different properties of bone strength, a prominent determinant of resistance to fracture, in 8-mo-old osteoporotic rats. Bone strength describes the greatest force, or load, which can be applied to a bone before a fracture occurs.…”
Section: Discussionmentioning
confidence: 99%